Sistem Kartu Ujian Online Menggunakan Framework Yii Pada Universitas Raharja - Immaniar, Dewi; Cholisoh, Novi; Eka Putra, Fajar Januar; Pangestu, Prisilia Santoro; Sunarya, PO Abas; Immaniar1, Dewi; Sunarya, Sunarya (Technomedia Journal, 2022)
The process of making an exam card every semester change is to combine several components consisting of students, lecturers, space, time and payment. Making a test card requires time, effort and accuracy in making it and also a very long process which is around one week because it is still manual alias old school, to be able to produce an exam card from the RPU must first make an exam schedule the data is taken from OJRS + data. This research makes the broadcasting of online test cards using YII Framework. This can be a problem because there is still a risk of conflict. All of these problems can be solved by a system that can create schedules automatically or online. With this will discuss how to build an automatic scheduling application starting from needs analysis to how a scheduling problem can be solved. Keywords: Optimization, online, Test Card, bootstrap framework